Formulation of Restorative Justice-Based Law Enforcement Policy for Children in Conflict with Law - Dicky Erizon; Andi Suhendra; Fadlan Fadlan; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the formulation of restorative justice-based law enforcement policies for children in conflict with law, focusing on the development and implementation challenges within the juvenile justice system. Using a qualitative descriptive-analytical approach, the study analyzes current policy frameworks, implementation practices, and systemic challenges through comprehensive literature review, in-depth interviews with key stakeholders, and focus group discussions with legal practitioners and child protection experts. The findings reveal that while the legal framework for restorative justice exists, implementation faces significant challenges including limited understanding among law enforcement officers, inadequate infrastructure, and insufficient inter-agency coordination. The study also identifies successful practices and proposes a comprehensive policy framework that emphasizes capacity building, institutional strengthening, and community engagement. This research contributes to the development of more effective and child-centered approaches in juvenile justice systems, providing practical recommendations for policy makers and law enforcement agencies in implementing restorative justice principles for children in conflict with law.